2022
DOI: 10.1186/s12877-022-02997-6
|View full text |Cite|
|
Sign up to set email alerts
|

Two-megahertz impedance index prediction equation for appendicular lean mass in Korean older people

Abstract: Background Whole-body bioelectrical impedance analysis (BIA) has been accepted as an indirect method to estimate appendicular lean mass (ALM) comparable to dual-energy X-ray absorptiometry (DXA). However, single or limited frequencies currently used for these estimates may over or under-estimate ALM. Accordingly, there is a need to measure the impedance parameter with appendicular lean-specific across multiple frequencies to more accurately estimate ALM. We aimed to validate muscle-specific fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The interpretation of data evaluated by the BIA begins to be dubious due to the fact that there are studies that do not demonstrate correlations of results between different BIA devices (Kim et al 2022, Lee et al 2017. For example, the predictive equations of the InBody230® scale for evaluating FM and SMM are not publicly available and cannot be manipulated by users.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of data evaluated by the BIA begins to be dubious due to the fact that there are studies that do not demonstrate correlations of results between different BIA devices (Kim et al 2022, Lee et al 2017. For example, the predictive equations of the InBody230® scale for evaluating FM and SMM are not publicly available and cannot be manipulated by users.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of bias was high in two [34,35] and unclear in six [36][37][38][39][40][41] studies due to the low to moderate (R 2 < 80%) coefficient of determination (R 2 ) resulted from the multiple regression models. Concerns with applicability were high in 19 studies [37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and unclear [41,50,[60][61][62][63][64][65][66][67][68][69] in 12 studies due to the restricted sample size.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…A total of 885 males and 396 females were included in 11 studies [31,39,48,51,62,69,[83][84][85][86][87][88] aimed to develop predictive equations for athletes. A total of 1469 males and N = 2111 females were included in 17 studies [36,38,46,53,60,63,67,68,[89][90][91][92][93][94][95][96][97] aimed to develop predictive equations for elderly people. A total of 358 males, 637 females, and 75 subjects without sex designated were included in 8 studies [35,40,41,56,64,65,98,99] aimed to develop predictive equations for people with diseases.…”
Section: Participantsmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in this article the author Fang Lin Jiang was incorrectly linked to affiliations 6 and 7, but should have been linked to affiliation 6 only; and the author Chul-Hyun Kim was incorrectly linked to affiliation 7, but should have been linked to affiliation 6.…”
mentioning
confidence: 99%